Demographics, labor market power and the spatial equilibrium - Nina Furbach (European Central Bank (ECB), 2024)
This paper studies how demographics affect aggregate labor market power, the urban wage premium and the spatial concentration of population, I develop a quantitative spatial model in which labor market competitiveness depends on the demographic composition of the local workforce, Using highly disaggregated administrative data from Germany, I find that firms have more labor market power over older workers: The labor supply elasticity decreases from more than 2 to 1 from age 20 to 64, Calibrating the model with the reduced-form elasticity estimates, I find that differences in labor supply elasticities across age groups can explain 4% of the urban wage premium and 2% of the spatial concentration of population, Demographics and skill together account for 10% of the urban wage premium and 2% of agglomeration.
Keywords: J11; J31; J42; R23; 330; Monopsonistic competition; urban wage premium; demographics; Germany; spatial equilibrium